Analisis Penerapan Hak Kekayaan Intelektual Menjadi Jaminan dalam Perbankan (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The Indonesian government in supporting Intellectual Property actors has issued Government Regulation Number 24 of 2022 concerning the Implementation of Law Number 24 of 2019 concerning the Creative Economy As a maximum effort in implementing Government Regulation No. 24 of 2022 concerning the creative economy in helping to strengthen national and international economic development, but the regulation only regulates generally regarding Intellectual property, furthermore it is deemed necessary to have more specific regulations specifically regarding asset quality ratings as collateral which is expected to be not only for financing institutions but can help Intellectual Property assessment institutions, considering that Intellectual Property is an intangible object that makes banks as creditors hesitate to accept Intellectual Property as collateral in financing. The basic reason Intellectual Property Rights can be used as fiduciary collateral because it is included in the law of immaterial objects where one of the characteristics of objects that can be used as debt collateral is objects that have economic value, copyright is also attached to exclusive rights, namely the attachment of these rights to the creator or holder of the copyright he created.